Potential of higher plants, algae, and cyanobacteria for remediation of radioactively contaminated waters. (September 2018) - Vanhoudt, Nathalie; Vandenhove, Hildegarde; Leys, Natalie; Janssen, Paul
Abstract: The potential of photosynthetic organisms to remediate radioactively contaminated water was evaluated for scenarios related to nuclear installations and included the following radionuclides: 137 Cs, 134 Cs, 136 Cs, 90 Sr, 131 I, 239 Pu, 241 Am, 132 Te/ 132 I, 58 Co, 60 Co, 51 Cr, 110m Ag, 54 Mn, 124 Sb, 59 Fe, 65 Zn, 95 Zr, and 95 Nb. An extensive literature review was undertaken leading to the creation of a database including more than 20, 000 entries from over 100 references in which terrestrial and aquatic plants, macro- and microalgae, cyanobacteria and biosorbents derived from these organisms were used to clean water from these specific radionuclides or their stable isotopes. In a first phase, the remediation potential of the organisms and biosorbents was evaluated for the individual elements based on parameters such as plant uptake, removal percentage, and bioconcentration factor, and for two radionuclide mixtures based on the ability of the organisms/biosorbents to work under mixture conditions. As the experimental and environmental conditions will influence the performance of the organisms and biosorbents, a literature-based evaluation of the most influencing or restricting parameters was made and water pH, competing ions, and the chemical modification of biosorbents showed to be of major importance. Finally, the most promising organisms and biosorbents were identified using a specifically developed selection procedure taking into account their performance and robustness. Ranking was done based on clear criteria with a distinct weight and scoring scheme. As such, 20 organisms/biosorbents were identified that showed high potential to clean waters contaminated with (mixtures of) radionuclides related to nuclear installations and which can be used for further experimental investigations. Graphical abstract: Image Highlights: Photosynthetic organisms show potential to clean radioactively contaminated water. 8 organisms/biosorbents selected for mixture Cs, Sr, I, Pu, Am and Te. 12 organisms/biosorbents selected for mixture Co, Cr, Ag, Mn, Sb, Fe, Zn, Zr and Nb. pH, competing ions and chemical modification biosorbents most influential factors.